Neurovascular bundle dissection for Nesbit procedure in congenital penile curvature patients: medial or lateral? - Akbulut, Fatih (Medknow Publications & Media Pvt Ltd, 2014)
The objective of this study was to compare the outcomes of the modified Nesbit procedure using different techniques for dissecting the neurovascular bundle (NVB) to correct ventral congenital penile curvatures (CPCs). The bundle was mobilized using the medial and lateral dissection technique in 21 (Group 1) and 13 (Group 2) patients, respectively. In the medial technique, Buck's fascia is opened at the dorsal side of the penis, the deep dorsal vein is removed at the most prominent site of the curvature and a diamond-shaped tunica albuginea (TA) is excised from the midline of the penis. In the lateral technique, the bundle is mobilized using a longitudinal lateral incision of the Buck's fascia above the urethra at the 5 and 7 o’clock positions via a bilateral approach. The localization and degree of curvature was evaluated using the combined intracavernous injection stimulation test or from the patients’ photographs. The mean patient age and degree of curvature were similar between groups. The mean operation time was longer for Group 2 (P = 0.01). In Group 1, nine patients (42.8%) required one diamond excision, 10 (47.6%) required two diamond excisions and two (9.5%) required more than two excisions; in Group 2, six patients (46.2%) required two diamond excisions and seven patients (53.8%) required more than two diamond excisions (P = 0.019). The differences in penile shortening, penile straightening and numbness of the glans penis were not statistically significant. Medial dissection of the bundle for the modified Nesbit procedure reduces the number of diamond-shaped removals of TA and thus shortens operation time in comparison with its lateral counterpart.